Search for vector-boson resonances decaying into a top quark and a bottom quark using pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; et al. (Journal of high energy physics, 2023)
A search for a new massive charged gauge boson, W′, is performed with the ATLAS detector at the LHC. The dataset used in this analysis was collected from proton-proton collisions at a centre-of-mass energy of √s = 13 TeV, and corresponds to an integrated luminosity of 139 fb−1. The reconstructed tb invariant mass is used to search for a W′ boson decaying into a top quark and a bottom quark. The result is interpreted in terms of a W′ boson with purely right-handed or left-handed chirality in a mass range of 0.5-6 TeV. Different values for the coupling of the W′ boson to the top and bottom quarks are considered, taking into account interference with single-top-quark production in the s-channel. No significant deviation from the background prediction is observed. The results are expressed as upper limits on the W′ → tb production cross-section times branching ratio as a function of the W′-boson mass and in the plane of the coupling vs the W′-boson mass.